2008
DOI: 10.1007/s12205-008-0197-7
|View full text |Cite
|
Sign up to set email alerts
|

A model to estimate the marginal walking time of bus users by using adaptive neuro-fuzzy inference system

Abstract: As bus users give up riding buses and choose the other alternatives when walking times to bus stops are longer than their marginal walking time, whether the bus stops are available within the marginal walking time at origin and destination of their travel affects definitely to bus users' bus service selection. Therefore, bus service coverage area should be decided considering reasonable walking distance or time from bus stops. In this study, an ANFIS model to estimate the marginal walking time was constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Thus, it is indicated that transit agencies in the United States may accordingly enlarge stop spacing as advocated in the existing research [9,16], where acceptable stop spacing for the rail service is largest, while that for the R-A and NR-A bus service is similar. Thus, this research adds to the literature with an exploration of the vertex of acceptable transit stop spacing based on the inference from the observable transit walk time, instead of empirical statistics [9,10], optimization analysis [20], or a revealed preference survey [27][28][29][30]. Moreover, the result extends previous literature with categorized transit service, finding that the NR-A bus service has the largest gap between the actual stop walk time and its vertex, while the R-A bus service has the smallest.…”
Section: Model Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is indicated that transit agencies in the United States may accordingly enlarge stop spacing as advocated in the existing research [9,16], where acceptable stop spacing for the rail service is largest, while that for the R-A and NR-A bus service is similar. Thus, this research adds to the literature with an exploration of the vertex of acceptable transit stop spacing based on the inference from the observable transit walk time, instead of empirical statistics [9,10], optimization analysis [20], or a revealed preference survey [27][28][29][30]. Moreover, the result extends previous literature with categorized transit service, finding that the NR-A bus service has the largest gap between the actual stop walk time and its vertex, while the R-A bus service has the smallest.…”
Section: Model Resultsmentioning
confidence: 99%
“…Recently, delicate research has been implemented to account for the effect of passenger characteristics and service quality on transit stop spacing. With respect to passenger socio-economics, Kim et al [27] conducted a questionnaire to obtain passengers' sociodemographics and transit use information in various city types, including the factors of gender, age, employment status, income, car ownership, transit use frequency, trip purpose, and access mode [28]. With cross-sectional statistics and adaptive neuro-fuzzy inference model, it was found that age and income significantly influenced the maximum acceptable walk time to transit stops.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation